Worry About Caregiving Performance: A Confirmatory Factor Analysis - Li, Ruijie; Chong, Mei Sian; Chan, Peng Chew Mark; Tay, Bee Gek Laura; Ali, Noorhazlina Binte; Lim, Wee Shiong (Frontiers in Medicine, 2018)
Recent studies on the Zarit Burden Interview (ZBI) support the existence of a unique factor, worry about caregiving performance (WaP), beyond role and personal strain. Our current study aims to confirm the existence of WaP within the multidimensionality of ZBI and to determine if predictors of WaP differ from the role and personal strain. We performed confirmatory factor analysis (CFA) on 466 caregiver-patient dyads to compare between one-factor (total score), two-factor (role/personal strain), three-factor (role/personal strain and WaP), and four-factor models (role strain split into two factors). We conducted linear regression analyses to explore the relationships between different ZBI factors with socio-demographic and disease characteristics, and investigated the stage-dependent differences between WaP with role and personal strain by dyadic relationship. The four-factor structure that incorporated WaP and split role strain into two factors yielded the best fit. Linear regression analyses reveal that different variables significantly predict WaP (adult child caregiver and Neuropsychiatric Inventory Questionnaire (NPI-Q) severity) from role/personal strain (adult child caregiver, instrumental activities of daily living, and NPI-Q distress). Unlike other factors, WaP was significantly endorsed in early cognitive impairment. Among spouses, WaP remained low across Clinical Dementia Rating (CDR) stages until a sharp rise in CDR 3; adult child and sibling caregivers experience a gradual rise throughout the stages. Our results affirm the existence of WaP as a unique factor. Future research should explore the potential of WaP as a possible intervention target to improve self-efficacy in the milder stages of burden.